2022
DOI: 10.1186/s13104-022-06032-0
|View full text |Cite
|
Sign up to set email alerts
|

Meary angle for the prediction of mitral valve prolapse risk in non-syndromic patients with pes planus, a cross-sectional study

Abstract: Objectives Mitral Valve Prolapse (MVP) is a common valvular abnormality accounting for 2% of the population. There is a reported association between pes planus (PP) and MVP in some syndromes such as Marfan. However, this association has not been tested in non-syndromic cases. The primary outcome of this study is to measure the prevalence of MVP in a population of patients with PP. The secondary outcome parameter is to determine if the Meary angle (MA), a measure of the severity of flat foot, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…Additionally, it is also known that cardiac pathologies can accompany thoracic and spinal skeletal anomalies [20][21][22]. AbdelMassih et al, emphasized in their study that the risk of MVP increases with the degree of FPP [8]. In our study, it was found that the risk of cardiac pathology in patients diagnosed with FPP is higher compared to normal individuals, similar to what is observed in connective tissue diseases, and a result consistent with the literature was obtained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it is also known that cardiac pathologies can accompany thoracic and spinal skeletal anomalies [20][21][22]. AbdelMassih et al, emphasized in their study that the risk of MVP increases with the degree of FPP [8]. In our study, it was found that the risk of cardiac pathology in patients diagnosed with FPP is higher compared to normal individuals, similar to what is observed in connective tissue diseases, and a result consistent with the literature was obtained.…”
Section: Discussionmentioning
confidence: 99%
“…As it is well-established, individuals with hypermobility syndromes may present with concomitant heart conditions, with mitral valve prolapse (MVP) being a noteworthy example [ 7 ]. In addition, it has been demonstrated that as the degree of FPP increases, the risk of concomitant MVP also increases [ 8 ]. Furthermore, in connective tissue disorders characterized by hypermobility such as Marfan syndrome and Ehler-Danlos syndrome, cardiac pathologies can also be encountered [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%